FEATURES OF SECURED INFORMATION NETWORK DESIGN - Khoroshko, Volodymyr; Laptiev, Oleksandr; Khokhlachоva, Yulia; Al-Dalvash , Abdullah; Pepa, Yurii (Science-based technologies, 2024)
The article deals with the design problems of secure information networks. The process of introducing new information technologies into all spheres of social life is unthinkable without solving the issues of information security, which is structured in completely different but interconnected aspects. Modern progress in the field of global networks and multimedia tools has led to the development of numerous methods designed to ensure the safe transmission of information through telecommunications channels and their use for undeclared purposes, methods of synthesis of various information objects and the development of their new mathematical models. The mathematical apparatus used in the field of information security has so far remained rather limited. Until now, there is no single mathematical approach to the analysis and processing of data about information objects, information transmission networks and their design methods. Due to the lack of a single mathematical apparatus, until now there were no methods for conducting an a priori analysis of the properties of these objects, comparing different technologies of the functioning of communication systems, which in general deprived the possibility of a reasonable choice of the technology of the functioning of the communication network or the method of its design. Therefore, it is extremely relevant to ensure the possibility of automated analysis of the state and functioning of protected communication networks, including the analysis of the functioning of the information system as a whole, taking into account the possibility of the emergence of both natural and artificial channels of information leakage and various types of influences, automatic processing of the results of such leakage and influences, choosing the way to restore the network after an attack, as well as to solve the issues of synthesis and design of protection systems of communication information networks with the involvement of modern mathematical apparatus is the creation of a unified mathematical approach to the problem of assessing the state of communication information networks, which would avoid their heterogeneous and poor formalizability by means of a computationally simple analysis of only a certain group of mathematical parameters describing the functioning of protected communication networks. This work is dedicated to solving this urgent problem.